Comparison The Value Of Bta Sputum Between Pulmonary Tuberculosis Patients With Diabetes Mellitus And Pulmonary Tuberculosis Patients Non-Diabetes Mellitus. - Bagas Setiawan Ihsan Zaini; Adyan Donastin; Lea Maera Shanty; Hotimah Masdan Salim (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2020)
Background & Aims: Tuberculosis (TB) is a health problem. Based on the WHO report in 2016, Indonesia is a developing country with the second largest TB case. One risk factor for pulmonary tuberculosis is having a history of diabetes mellitus disease. The aim of this research is to examine the differences the value of BTA sputum between pulmonary TB patients with diabetes mellitus and pulmonary TB patients non-diabetes mellitus.Methods: This research is descriptive analytic with comparative study. This study uses secondary data in Islamic Jemursari Surabaya Hospital period January - December 2017. The results will be processed using descriptive analysis and Mann-Whitney test with SPSS 25.00 for windows.Results: This research obtained 68 samples consisting of 34 the pulmonary TB non-diabetes mellitus and 34 pulmonary TB with diabetes mellitus. In pulmonary TB patients non-diabetes mellitus most have negative BTA sputum values, while pulmonary TB with diabetes mellitus is positive (+1), so there are differences in the value of BTA sputum with a significance value 0.001 (<0.05).Conclusion: There is a difference in the value of BTA sputum between pulmonary TB patients with diabetes mellitus and pulmonary TB patients non-diabetes mellitus. It caused in patients with diabetes mellitus have immunological abnormalities, especially IFN-γ and pulmonary physiological disorder.